Formulation and Physical Stability Testing of Exfoliating Gel and Moisturizing Gel From Sugarcane Bagasse Extract - Iin Suhesti; Ester Dwi Antari; Syafa Chasna Nasrina; Marzela Pancaya Putra (International Journal of Health and Pharmaceutical (IJHP), 2025)
Sugarcane bagasse extract (Saccharum officinarum Linn.) has high antioxidant activity due to its phenolic compounds, which are beneficial for moisturizing dry skin, smoothing the skin, and combating free radicals. This study aimed to evaluate the physical stability of exfoliating and moisturizing gel formulations containing sugarcane bagasse extract at concentrations of 1%, 3%, and 5% using the cycling test method over six cycles (12 days) at temperatures of ±4°C and ±40°C. Parameters tested included organoleptic properties, homogeneity, pH, viscosity, spreadability, and adhesiveness. The results showed that the formulations without extract (control) and those with 1% extract concentration met the physical stability parameters and remained stable throughout the cycling test, with viscosity ranging from 13,665.7 to 20,180.6 cPs, pH between 4.76 and 5.43, spreadability from 3.25 to 5.64 cm, and adhesiveness from 0.42 to 1.52 seconds. In contrast, formulations with 3% and 5% extract concentrations exhibited physical instability, such as changes in pH, viscosity, and spreadability, failing to pass the stability test cycles.